Identification Correlation of Cloud to Ground Lightning Type Activity with Rainfall around Sanglah Climatology Station in 2018 - Reswari, Lintang Ardhana; Sukarasa, I Ketut; Pratama, I Putu Dedy (BULETIN FISIKA; Vol 22 No 2 (2021): BULETIN FISIKA August EditionDO - 10.24843/BF.2021.v22.i02.p07, 2021)
Denpasar has a high lightning hazard. CG (Cloud to Ground) lightning type is the lightning that have a direct impact to human. This study aims to determine the relationship between the amount of lightning strikes and rainfall that occurred in BMKG Sanglah on 2018. The data used are rainfall data obtained from Automatic Rain Gauge (ARG) and Cloud to Ground (CG) lightning data from lightning detectors installed at BMKG Sanglah Denpasar. CG lightning data (positive and negative) is limited within a 5 km radius of sensor. The lightning and precipitation data obtained then looked at the correlation using spearman correlation test to find out the relationship between rainfall and lightning The results obtained show the relationship between daily and monthly rainfall and CG lightning with Spearman correlation of 0,372 and 0.834, which means that the relation between the two variables has proportionate correlation where rainfall is bigger than lightning will also.